PENGARUH CUSTOMER EXPERIENCE TERHADAP REPURCHASE INTENTION MELALUI KEPUASAN PELANGGAN PADA E-COMMERCE SHOPEE - Syarifa Diyanti, (2021)
By using qualitative method, this research aims to analyze and prove the direct effect of customer experience and customer satisfaction towards repurchase intention, as well as the indirect effect of customer experience towards repurchase intention through customer satisfaction. The population used for this research is the users of e-commerce Shopee in Jakarta with the total sample of 100 respondents. This research used non-probability sampling technique which is purposive sampling and the data collection was disseminated by google form through the social media community. Using index number of descriptive analysis technique along with partial least square as the inferential analysis technique by using Smart PLS 3.3.3 analysis tool, the result shows that customer experience and customer satisfaction have a significant effect towards repurchase intention, while on the other hand customer experience have an indirect significant effect towards repurchase intention through customer satisfaction.